2019
DOI: 10.1002/sctm.18-0255
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Derived from Genetically Modified Human Induced Pluripotent Stem Cells Circulate and Phagocytose Bacteria In Vivo

Abstract: Bacterial and fungal infections are a major cause of morbidity and mortality in neutropenic patients. Donor‐derived neutrophil transfusions have been used for prophylaxis or treatment for infection in neutropenic patients. However, the short half‐life and the limited availability of large numbers of donor‐derived neutrophils for transfusion remain a significant hurdle in the implementation of neutrophil transfusion therapy. Here, we investigate the in vitro and in vivo activity of neutrophils generated from hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 60 publications
3
43
0
Order By: Relevance
“…11 Small molecules that can regulate ROS levels play an important role in differentiation of hematopoietic stem/progenitor cells from human pluripotent stem cells (hPSCs), especially in the serum-and stroma cell-free hematopoietic differentiation system. 12 Modulation of ROS level enhances development of CD34 + cells derived from hPSCs, 13 indicating that high ROS levels might cause apoptosis of hemogenic from hPSCs such as NK cells, 15 T lymphocytes, 16 erythrocytes, 17 neutrophils, 18,19 and M s 20 has been reported widely, recent research has focused on the molecular regulation and applications of hematopoietic cell differentiation from hPSCs. Two main methods are used for hematopoietic differentiation of human pluripotent stem cells: coculture with stroma cells and embryoid body formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Small molecules that can regulate ROS levels play an important role in differentiation of hematopoietic stem/progenitor cells from human pluripotent stem cells (hPSCs), especially in the serum-and stroma cell-free hematopoietic differentiation system. 12 Modulation of ROS level enhances development of CD34 + cells derived from hPSCs, 13 indicating that high ROS levels might cause apoptosis of hemogenic from hPSCs such as NK cells, 15 T lymphocytes, 16 erythrocytes, 17 neutrophils, 18,19 and M s 20 has been reported widely, recent research has focused on the molecular regulation and applications of hematopoietic cell differentiation from hPSCs. Two main methods are used for hematopoietic differentiation of human pluripotent stem cells: coculture with stroma cells and embryoid body formation.…”
Section: Introductionmentioning
confidence: 99%
“…While regeneration of functional hematopoietic cells derived from hPSCs such as NK cells, 15 T lymphocytes, 16 erythrocytes, 17 neutrophils, 18,19 and Mϕs 20 has been reported widely, recent research has focused on the molecular regulation and applications of hematopoietic cell differentiation from hPSCs. Two main methods are used for hematopoietic differentiation of human pluripotent stem cells: coculture with stroma cells and embryoid body formation.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond their value for disease modeling, corrected iPSC-derived neutrophils and macrophages could be used as alternative autologous cell sources to combat intractable infections in CGD patients. In two different studies, iPSC-derived neutrophils or macrophages were successfully applied to treat bacterial infections of the peritoneum or the lung (Trump et al., 2019, Ackermann et al., 2018). Recently, the application of CRISPR-RNPs in combination with an AAV6 to deliver the donor template has yielded high HDR rates (60%–70%) during gene editing of HSCs (Vakulskas et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In their recent Stem Cells Translational Medicine article, Trump et al first reprogrammed peripheral blood mononuclear cells into iPSCs and then generated neutrophils from iPSC‐derived hematopoietic cells. Interestingly, the authors discovered that while their iPSC‐derived neutrophils produced reactive oxygen species at a similar level to normal peripheral blood neutrophils, they displayed a significant reduction in the phagocytosis of Escherichia coli ( E. coli ) bacteria and the induced formation of neutrophil extracellular traps . Subsequent analysis suggested that impaired AKT (protein kinase B) activity in iPSC‐derived neutrophils prompted these functional discrepancies, although the expression of a constitutively activated AKT restored most phagocytic activity and neutrophil extracellular trap formation.…”
Section: Featured Articlesmentioning
confidence: 99%
“…Can the differentiation of neutrophils from induced pluripotent stem cells (iPSCs) provide the substantial number of neutrophils required for transfusions? In our second Featured Article from Stem Cells Translational Medicine this month, Trump et al provide proof‐of‐concept for the efficient differentiation of human iPSCs into neutrophils that phagocytose bacteria in vitro and in vivo . In a Related Article from Stem Cells , de Witte et al tracked MSCs following intravenous infusion, discovering that monocytes, another phagocytic cell type with crucial roles in the immune system, engulf MSCs in the lungs and then migrate to other body sites to mediate, distribute, and transfer the immunomodulatory effect of MSCs .…”
mentioning
confidence: 99%